(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
By providing intelligent capabilities to objects the physical objects communicate each other without human intervention in Internet of Things (IoT) environment. And these devices generate enormous traffic as the sum of IoT gadgets is increased. As the network traffic is irregular it is most important to obtain an optimal load balance among all the nodes. In this paper, we propose to develop a cache based multipath load balancing protocol for IoT sensor networks. In this protocol multiple paths are established between each IoT sender and the server such that each sender has multiple next-hop delivering IoT data. Whenever, the load of the server becomes greater than a threshold, the server transmits the overloaded high priority data to these cache points and the IoT clients can fetch the data from the nearby CPs rather than the server. The outcome of simulation had proved that CBMLB mechanism attains maximum ratio of packet delivery with reduced overhead and delay.